2014
DOI: 10.1097/jcn.0b013e3182a37789
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Delay in Seeking Care for Acute Decompensated Heart Failure

Abstract: The response of patients (wait-and-see) and others (eg, don't worry) contributed to delay, as did living in a rural environment. Evaluative characteristics of attribution and understanding were not significant determinants of delay, suggesting that patient education alone will not effectively decrease delay. Instead, interventions directed toward decision making in response to symptoms and inclusion of family members in such discussions may be more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 49 publications
1
59
2
Order By: Relevance
“…The mean HFSPS score in this study was higher than similar studies in the United States and Italy, along with another study that used this scale for a different purpose in China [12,31,[33][34][35]. In addition, the HFSPS was used to examine patients' physical symptoms in China as well [31].…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…The mean HFSPS score in this study was higher than similar studies in the United States and Italy, along with another study that used this scale for a different purpose in China [12,31,[33][34][35]. In addition, the HFSPS was used to examine patients' physical symptoms in China as well [31].…”
Section: Discussioncontrasting
confidence: 50%
“…Meanwhile, as reported in prior studies, the higher NYHA functional class level and LVEF level indicated that more symptoms were experienced [38,39]. Symptom clusters, even in different cultural groups, were found to be significantly related to symptom perception [35,40,41]. A study reported that symptom education could significantly improve patients' short-term prognosis [42].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Normalizing symptoms allowed patients to minimize the impact of their illness and continue with normal life activities such as returning to work to meet their financial needs. Although normalizing symptoms may have also helped patients to maintain a sense of routine life and continuity, normalizing prevented patients from the understanding that they were living with a life-threatening illness [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, patients who live alone may be unable to get to the ED at night, or on the weekends due to availability of family or friends to transport them to the ED and other factors such as patient preferences may play a role in mode of transportation. 21 Prehospital delay has also not been linked to clinical outcomes; however, patients with <24 h since symptom onset have a lower BNP and a shorter length of stay. 22 Indeed, when added to the multivariable model, these factors were not independently significant predictors of clinical outcomes in ASCEND-HF.…”
Section: Discussionmentioning
confidence: 99%